Screen based activity sebagai faktor risiko kegemukan pada anak prasekolah - Neni Pangesti; I Made Alit Gunawan; Madarina Julia (Jurnal Gizi Klinik Indonesia, 2016)
Background: Obesity in children increased health risk and the high cost of treatment of obesity. Extensive screen based activity (SBA) are sedentary behavior which is contributing to childhood obesity. Objective: to analyze the risk of the duration of SBA with obesity among preschool children in Yogyakarta city. Method: The study design was case-control study between obese and non-obese preschool children. A hundred and one pairs (obese and non-obese) subjects aged 3-5 years old who enrolled in preschools in Yogyakarta was obtained from screening. The school was selected using Probability Proportional to Size method. The case and control were matching by age and gender. Obesity was defined by WHZ-score > 2 SD. Preschool Physical Activity Questionnaire (PrePAQ) was used to collect the information on duration of SBA. Data duration SBA asked at weekdays and weekend. Data was analyzed using t-test and conditional logistic regression test. Results: children duration of SBA at weekend and parents duration of SBA were not statistically associated with obesity occurrence in children (p>0, 05). Obese children spent 48 minutes longer engaged in SBA compared to the non-obese children in weekdays.Conclusion: Children duration of SBA at weekdays could increase the risk of obesity occurrence among preschool children in Yogyakarta